PERBANDINGAN PENDAPATAN PETANI KOPRA JEMUR DAN KOPRA ASAP (STUDI KASUS DESA PASLATEN SATU KECAMATAN TATAPAAN) - Neprianus ., Siloto; Welson M. Wangke; Theodora M. Katiandagho (Sam Ratulangi University, 2017)
This study aims to see the comparison of income that is located in Paslaten Village between copra clay farmers and dried copra farmers. This research was conducted in March 2016 until August 2016. The data used in this research is using direct interview with 10 (Ten) ie 5 respondents of Copra smoke farmer and 5 respondents of Copra Drying farmers. The data obtained will be tabulated and analyzed in a quantitative and descriptive way. The results of this study indicate the average total income of peanut copra farmers is Rp. 5,371,671.26 in one production, while the average total income of dried coconut copper is Rp. 2,533,740.30 in one production.